2016
DOI: 10.7324/japs.2016.60403
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pfmdr 1 N86Y and Y184F Alleles is Associated with Recurrent Parasitemia following Treatment of Uncomplicated Malaria with Artemether-Lumefantrine in Nigerian Patients

Abstract: We investigated and compared genetic variations in Plasmodium falciparum multidrug resistance 1 gene (Pfmdr 1) in patients showing good therapeutic response (GTR) and artemisinin resistance (AR) following artemetherlumefantrine (AL) treatment of uncomplicated malaria in Nigeria. Some 150 malaria patients were subjected to AL treatment and therapeutic efficacy was monitored for 28 days. Parasite genomic DNA was isolated followed by nested polymerase chain reaction (PCR). Genotyping of Pfmdr 1 gene for specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Results from this study has shown prevalence of pfmdr-1 Y86, F184 and Y1246 mutant type as 27%, 56% and 48% respectively. This is close to the result of a recent study in Enugu State, Nigeria by Emilia et al, [31] where they associated these alleles to AL treatment failure. Equally, Agomo et al, [10] reported pfmdr-1 Y86 of 25% in their study to assess markers of antimalarial drug resistance among pregnant women in Lagos.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results from this study has shown prevalence of pfmdr-1 Y86, F184 and Y1246 mutant type as 27%, 56% and 48% respectively. This is close to the result of a recent study in Enugu State, Nigeria by Emilia et al, [31] where they associated these alleles to AL treatment failure. Equally, Agomo et al, [10] reported pfmdr-1 Y86 of 25% in their study to assess markers of antimalarial drug resistance among pregnant women in Lagos.…”
Section: Discussionsupporting
confidence: 90%
“…The surveillance of molecular markers as useful predictors of emerging or existing levels of resistance have proven important in recent years where reports on pfcrt have shown recovery of CQ sensitivity in Malawi [28]. Pfmdr-1 is implicated in resistance or tolerance to most antimalarial drugs including chloroquine (CQ), amodiaquine (AQ) and the artemisinin derivates; consequently, certain combinations of its SNPs at codons 86, 184, and 1246 are indicated to have emerged in areas where artemether-lumefantrine (AL) is being widely used [29,30,31], suggesting that these haplotypes may be suspects in the decreased ACTs efficacy. In Nigeria, despite few studies had been done on the prevalence of these resistant markers, Happi et al, [21] reported 40% prevalence of pfmdr1 Y86 in a study on the efficacy of CQ to treat uncomplicated malaria in young children at Ibadan.…”
Section: Discussionmentioning
confidence: 99%